Pengaruh Gaya Hidup Konsumtif dan Promosi Penjualan terhadap Keputusan Pembelian - Evi Rachmawati; Anik Lestari Andjarwati (Universitas Jember, 2019)
The emergence of various types of fastfood with the predominance of American-style restaurants is very intense in Indonesia. This proves that foreign restaurants are quite popular among Indonesian people. Accompanied by the influence of westernization (westernized behavior) that makes consumption patterns that accentuate luxury, pleasure and spree spending money are enough to influence people’s lifestyle today. The company’s strategy competition in fighting over the market becomes very tough, so they are competing to improve their company strategy. Population of this research is consumer of Burger King in Surabaya. The sampling method of this research was non-probability sampling with judgemental sampling method with a total sample of 220 respondents. This research instrument used an offline questionnaire with likert scale while multiple linear regression were used in order to analysis the dat. The result of this research indicate that consumptive lifestyle have a significant positive effect toward purchase decision, and sales promotion have a significant positive effect toward purchase decision. But in this research value shows that sales promotion variable has larger influence. Keywords: Consumptive Lifestyle, Purchase Decision, Sales Promotion